Siss/Unn/ingen: The Queer Revenant in Is-slottet - Olivia Noble Gunn (Edda)
Abstract This essay locates a queer revenant in The Ice Palace. The attraction between main characters Siss and Unn clearly evokes lesbianism for many critics, but lesbianism is quickly dismissed as having little analytical value for understanding the novel. Drawing on lesbian studies, I follow the traces of same-sex desire throughout the novel to argue that they have a good deal in common with familiar figurations of lesbianism that often manifest as fantastical, revivable corpses.